The eventual successful management of ovarian torsion in a hyperstimulated ovary following in vitro fertilization: A case report - Gordon Narayansingh; Jennifer Hoh (Elsevier, 2020)
Abdominal pain following in vitro fertilization (IVF) in the presence of enlarged ovaries commonly leads to the diagnosis of ovarian hyperstimulation syndrome (OHSS). Progressively worsening pain with a rise in inflammatory markers with normal hematological indices implies a diagnosis of ovarian torsion of the hyperstimulated ovary. Early recourse to laparoscopic assessment and derotation of the affected ovary even after 72 h following the onset of symptoms can allow a return to viability. This case highlights the clinical scenario and sequences in a successful outcome. Keywords: Ovarian torsion, In Vitro fertilization, Ovarian hyperstimulation yndrome, Laparoscopy